Social control and self-control: factors linking exposure to domestic violence and adolescents’ Internet gaming addiction - Li Quancai; Cui Meng; Cui Kunjie (Frontiers in Psychiatry, 2023)
Although many studies have investigated the influencing factors of adolescents’ Internet gaming addiction, few have investigated the influence factor of exposure to domestic violence, and even fewer have used the General Strain Theory to explain the influence path of exposure to domestic violence on adolescents’ Internet gaming addiction. Based on the GST, this study sought to uncover further insights into the effect of exposure to family violence on adolescents’ Internet gaming addiction, and the mediating role of social control—specifically, parental attachment—and self-control in the association between exposure to family violence and adolescents’ Internet gaming addiction. Adopting a multi-stage cluster random sampling method, we conducted this study with 2,110 adolescents from Liangshan Yi Autonomous Prefecture in Sichuan Province, China. The results suggest that adolescents’ exposure to domestic violence directly affects their addiction to Internet games and indirectly affects it by decreasing social control and self-control. The study not only supplements and improves the explanatory framework of General Strain Theory, but makes a significant contribution to research on the causes of Internet gaming addiction.